Association of semi-quantitative cryptococcal antigen results in plasma with subclinical cryptococcal meningitis and mortality among patients with advanced HIV disease. (25th June 2021) - Blasich, Nozuko P; Wake, Rachel M; Rukasha, Ivy; Prince, Yvonne; Govender, Nelesh P
Abstract: Blood cryptococcal antigen (CrAg) titers >160 are associated with concurrent subclinical cryptococcal meningitis (CM). When lumbar puncture (LP) is not immediately available in a CrAg screening program, semi-quantitative CrAg assays may provide risk stratification for CM. Two semi-quantitative assays (SQ [Immuno-Mycologics, Norman, OK, USA] and CryptoPS [Biosynex, Strasbourg, France]) were evaluated against a qualitative lateral flow assay (LFA) using 194 plasma samples from a cohort of HIV-seropositive individuals with CD4 counts <100 cells/μl. We compared SQ and CryptoPS results to titers for LFA-positive samples. Among patients with LP, we examined the association between semi-quantitative CrAg results and CM. We used a Cox proportional hazards model to determine the association between SQ score and mortality. Of 194 participants, 60 (31%) had positive LFA results, of whom 41 (68%) had a titer of ≤160 and 19 (32%) a titer >160. Fifty individuals with antigenemia had an LP; a clinically useful SQ score that identified all ten cases of subclinical CM was ≥3 (100% sensitivity, 55% specificity). Patients with an SQ score of 3 or 4 also had a 2.2-fold increased adjusted hazards of 6-month mortality (95% CI: 0.79–6.34; p = 0.13) versus those with score of <3. Nine of ten patients with subclinical CM had a strong-positive CryptoPS result versus 10/40 without subclinical CM (p < 0.001). Semi-quantitative assays offered a sensitive though not specific means of gauging the risk of concurrent CM in this patient population. Lay summary: We evaluated two single-step laboratory tests that can quantify the amount of cryptococcal antigen in plasma of patients with advanced HIV disease and could thus gauge the risk of concurrent cryptococcal meningitis and subsequent mortality. These tests are not a substitute for a lumbar puncture.